2022
DOI: 10.2478/jtim-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and connective tissue diseases: From bench to bedside

Abstract: The pathogenesis of connective tissue diseases (CTDs), represented by systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), systemic sclerosis (SSc), primary Sjögren’s syndrome (pSS), and idiopathic inflammatory myopathies (IIM), includes various immune cells involved in both innate and adaptive immunity. The mesenchymal stem cells (MSCs) are unique due to their regulatory effect on immunity. This makes them a promising therapeutic approach for patients with immune-mediated disorders such as CTD. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…By secreting various cytokines, SCs act on MCs and inhibit MMT to ameliorate PF. Several studies [40,41,[87][88][89] have demonstrated that SCs can produce a wide range of cytokines, such as hepatocyte growth factor (HGF), IL-6, IL-4, IL-10, TSG-6 and IDO. Table 2 lists the major cytokines secreted by SCs that mediate their functions and the corresponding receptors and receptor cells.…”
Section: Effects Of Stem Cell-derived Cytokinesmentioning
confidence: 99%
“…By secreting various cytokines, SCs act on MCs and inhibit MMT to ameliorate PF. Several studies [40,41,[87][88][89] have demonstrated that SCs can produce a wide range of cytokines, such as hepatocyte growth factor (HGF), IL-6, IL-4, IL-10, TSG-6 and IDO. Table 2 lists the major cytokines secreted by SCs that mediate their functions and the corresponding receptors and receptor cells.…”
Section: Effects Of Stem Cell-derived Cytokinesmentioning
confidence: 99%